Pathology of the malignant form of foot and mouth disease in swine. I. the natural disease - Morales, Gustavo A. (International Center for Tropical Agriculture, 1974)
Clinical and histological observations were made on pigs infected with Foot and Mouth Disease (FMD) on three separate pig farms in Colombia. Overall mortality rate was higher in young animals than adults. Approximately 159 fetuses were aborted. Nineteen (19) spontaneously FMD infected pigs were necropsied. Lesions were found as follows: pedal lesions in 17 (89.5 percent); myocardial necrsois in 16 (84.2 percent); snout lesions in 14(73.7 percent); somatic muscle necrosis in 13(68.4 percent); liver lesions in 11 (59.7 percent) and tongue lesions in 8 (42.1 percent). Arteritis of the coronary vessels was observed in 4 out of eight pigs necropsied in the third outbreak. Lesions in the brain, pancreas and hairy skin were less consistent than others. The suggestion is made that FMDV can be epitheliotropic, myotropic, or both, relative to epidemiological circumstances which will be discussed in a future paper of the present series.